Clinical markers for identifying cholinergic deficits in Parkinson's disease. Issue 2 (12th November 2014) - Müller, Martijn L.T.M.; Bohnen, Nicolaas I.; Kotagal, Vikas; Scott, Peter J.H.; Koeppe, Robert A.; Frey, Kirk A.; Albin, Roger L.; Stacy (Chair), Mark; Lang, Anthony; Napier, Celeste; Samuel, Michael; Strafella, Antonio; et al.
ABSTRACT Background Cholinergic projection systems degeneration is associated with dopamine nonresponsive features of Parkinson's disease (PD). Cholinergic deficits are variable in nondemented PD. Identification of cholinergic deficits in PD may help with selection of suitable patients for targeted cholinergic drug treatment in PD. The objective of this retrospective multivariate predictor analysis study was to identify clinical markers indicative of cholinergic deficits in PD patients, as assessed by acetylcholinesterase ([11C]PMP) positron emission tomography. Methods One hundred thirty‐seven PD patients (34 female) participated; median modified Hoehn and Yahr score was 2.5 (range, 1‐4), average age 65.6 ± 7.4 years, and average duration of motor disease symptoms of 6.0 ± 4.2 years. Subjects were dichotomized as "normocholinergic" or "hypocholinergic" based on a 5th percentile cutoff from normal for the basal forebrain‐cortical and pedunculopontine nucleus‐thalamic cholinergic projection systems. Previously identified clinical indices of cholinergic denervation were used for statistical prediction of cholinergic deficits. Logistic regression determined which risk factors predicted cholinergic deficits. Sensitivity, specificity, and accuracy were determined for the (combinations of) significant predictor variables. Results Forty‐nine (35.8%) hypocholinergic PD subjects were identified. The combination of rapid eye movement (REM) sleep behavior disorder (RBD) symptoms and fall history showed highest diagnostic accuracy (81.1%) for predicting combined thalamic and cortical cholinergic deficits. A combined assessment of 8.5 m walk time and lower score on the Montreal cognitive assessment scale provided diagnostic accuracy of 80.7% for predicting isolated cortical cholinergic denervation. Conclusion Assessment of clinical indices of cholinergic denervation may be useful for identifying suitable subjects for trials of targeted cholinergic drug treatments in PD. © 2014 International Parkinson and Movement Disorder Society